Oligomerization of the integrin αIIbβ3: Roles of the transmembrane and cytoplasmic domains - Li, Renhao (The National Academy of Sciences, 2001)
Integrins are a family of α/β heterodimeric membrane proteins, which mediate cell–cell and cell–matrix interactions. The molecular mechanisms by which integrins are activated and cluster are currently poorly understood. One hypothesis posits that the cytoplasmic tails of the α and β subunits interact strongly with one another in a 1:1 interaction, and that this interaction is modulated in the course of the activation of αIIbβ3 [Hughes, P. E., et al. (1996) J. Biol. Chem. 271, 6571–6574]. To examine the structural basis for this interaction, protein fragments encompassing the transmembrane helix plus cytoplasmic tails of the α and β subunits of αIIbβ3 were expressed and studied in phospholipid micelles at physiological salt concentrations. Analyses of these fragments by analytical ultracentrifugation, NMR, circular dichroism, and electrophoresis indicated that they had very little or no tendency to interact with one another. Instead, they formed homomeric interactions, with the α- and β-fragments forming dimers and trimers, respectively. Thus, these regions of the protein structure may contribute to the clustering of integrins that accompanies cellular adhesion.